2011
DOI: 10.2519/jospt.2011.3504
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Myofascial Trigger Point Manual Therapy Combined With a Self-Stretching Protocol for the Management of Plantar Heel Pain: A Randomized Controlled Trial

Abstract: Plantar fasciitis or plantar heel pain is the most common foot pain condition treated by healthcare providers. 28 It has been estimated that plantar fasciitis occurs in approximately 2 million Americans annually 10 and affects as much as 10% of the general population over the course of a lifetime. 29 In fact, some authors have reported that plantar fasciitis accounts for between 8% and 15% of foot complaints in nonathletic and athletic populations. 31,37 Plantar heel pain has a negative impact on foot-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
154
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 35 publications
(35 reference statements)
7
154
0
4
Order By: Relevance
“…Saban et al 6 used a combination of gastrocnemius myofascial release, neural mobilization, and self-stretching exercises, reporting a reduction of 38% on a visual analog pain scale. Renan-Ordine et al 7 have also reported a reduction in plantar pain resulting from a combination of manual therapy and self-stretching. Finally, Looney et al 20 observed a 53% improvement in pain intensity in patients who used an instrument for soft tissue mobilization and also stretched at home.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Saban et al 6 used a combination of gastrocnemius myofascial release, neural mobilization, and self-stretching exercises, reporting a reduction of 38% on a visual analog pain scale. Renan-Ordine et al 7 have also reported a reduction in plantar pain resulting from a combination of manual therapy and self-stretching. Finally, Looney et al 20 observed a 53% improvement in pain intensity in patients who used an instrument for soft tissue mobilization and also stretched at home.…”
Section: Discussionmentioning
confidence: 96%
“…Prescribed treatments have generally required a greater number of sessions per week, with previous studies reporting treatment regimens of 3 weekly sessions over a period of 3 weeks 5 or 4 weekly sessions over 4 weeks. 7 The ability to offer different treatment options is important to suit different patient requirements and to fit around patients who have limited time available for treatment. Hip strengthening is a simple and quick treatment, which should be incorporated into clinical treatment routines using MT to maximize the results of the intervention and improve outcomes in the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a major orthopedic injury that affects about 10% of the world's population at least once in life (2,3). PF is characterized by a non-in lammatory degeneration and pain under the heel and along the medial side of the plantar fascia (3,4). It occurs as a result of repetitive microtrauma at the origin of the medial tuberosity of the calcaneus (5,6).…”
Section: Introductionmentioning
confidence: 99%